1981
DOI: 10.1111/j.1365-2427.1981.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet, body size, age and temperature on growth rates in the amphipod Gammarus pulex

Abstract: Increase in body wet weight of Gammarus pulex fed on decaying elm leaves was followed to senescence and death. Growth in juveniles was approximately exponential; from birth to death it conformed to a logistic growth curve, with maximum absolute increments in weight about half-way through a life span of 350-450 days at 15''C. Some individuals lived longer, for up to 640-700 days. The instantaneous or specific growth rate was maximal near birth, at c. 5-6% wet wt day ', and declined exponentially with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 78 publications
7
113
0
Order By: Relevance
“…In terms of temperature, we expected an increase in growth with temperature up to a plateau, as reported for other aquatic invertebrates such as Gammarus pulex (L.) (e.g. Sutcliffe et al, 1981). According to Iversen (1979), at temperatures higher than 13°C the increase in consumption by S. personatum does not compensate for the increase in metabolic costs, causing a decrease in growth.…”
Section: Growthmentioning
confidence: 68%
See 1 more Smart Citation
“…In terms of temperature, we expected an increase in growth with temperature up to a plateau, as reported for other aquatic invertebrates such as Gammarus pulex (L.) (e.g. Sutcliffe et al, 1981). According to Iversen (1979), at temperatures higher than 13°C the increase in consumption by S. personatum does not compensate for the increase in metabolic costs, causing a decrease in growth.…”
Section: Growthmentioning
confidence: 68%
“…Those differences influence microbial decomposition (Canhoto & Grac¸a, 1996) and invertebrate feeding and growth (Canhoto & Grac¸a, 1996;Friberg & Jacobsen, 1999;Gonza´lez & Grac¸a, 2003). Invertebrate feeding and growth are also affected by temperature, as it is an important determinant of metabolism (Sutcliffe et al, 1981;Nolen & Pearson, 1993;Gonza´lez & Grac¸a, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The crustacean G. pulex is one of the most important invertebrate species in temperate streams, which is widely distributed throughout Europe (Holdich & Pöckl 2007), and can reach a density of 10,000 m -2 and has a continued mortality throughout the year (Welton, 1979). G. pulex feeds on a variety of debris, such as oak and elm leaves (Sutcliffe et al, 1981). Ditches with oak trees along the banks are common in the Netherlands, and there are also plenty of macrophytes and L. stagnalis in many of these ditches.…”
Section: Model Systemmentioning
confidence: 99%
“…Similarly, the vast majority of studies have emphasized the herbivorous nature of Gammarus spp. and their shredder functional feeding group classification (Moore 1977;Sutcliffe et al 1981), others showed a far richer food base and documented the facts of their predation on planktonic crustaceans (Anderson & Raasveldt 1974;MacNeil et al 1997;Wilheim & Schindler 1999). In addition, some study confirmed the predatory nature of amphipods and the use of animal component in the diet even in the presence of abundant and diverse plant food .…”
Section: Introductionmentioning
confidence: 60%